High-pressure carbon dioxide treatment alleviates browning development by regulating membrane lipid metabolism in fresh-cut lettuce. (April 2022) - Ma, Wanlu; Li, Jiaxing; Murtaza, Ayesha; Iqbal, Aamir; Zhang, Jiao; Zhu, Lijuan; Xu, Xiaoyun; Pan, Siyi; Hu, Wanfeng
Abstract: The influence of high-pressure carbon dioxide (HPCD) treatment on the browning of fresh-cut lettuce was investigated during storage at 4 °C. The browning degree, color, weight loss, browning-related enzymes, and components related to membrane lipid metabolism of fresh-cut lettuce were assessed during storage. The results showed that HPCD treatment slowed down the browning of fresh-cut lettuce. Polyphenol oxidase activity and total phenolic content of HPCD-treated group were reduced by 53.50% and 74.63%, respectively. In addition, HPCD treatment inhibited lipoxygenase activity and delayed membrane lipid peroxidation, thus decreasing PAL's stimulation by membrane lipid peroxidation products and further reducing the synthesis of phenolic. On the other hand, HPCD treatment maintained the structural integrity of the cell membrane and prevented the cell membrane compartmentalization from being broken due to cell membrane breakage by inhibiting phospholipase D activity, which avoided the contact between enzyme and phenol and delayed the oxidative browning.